2018
DOI: 10.1002/wsbm.1417
|View full text |Cite
|
Sign up to set email alerts
|

PharmGKB: A worldwide resource for pharmacogenomic information

Abstract: As precision medicine becomes increasingly relevant in healthcare, the field of pharmacogenomics (PGx) also continues to gain prominence in the clinical setting. Leading institutions have begun to implement PGx testing, and the amount of published PGx literature increases yearly. The Pharmacogenomics Knowledgebase (PharmGKB; www.pharmgkb.org) is one of the foremost worldwide resources for PGx knowledge, and the organization has been adapting and refocusing its mission along with the current revolution in genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
208
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 260 publications
(208 citation statements)
references
References 30 publications
0
208
0
Order By: Relevance
“…In our previous study [44], we revealed essential proteins associated with BC pathogenesis through deep analyses of genetic alterations, signaling pathways [52], protein-protein interaction networks [55, 56], protein expression [57, 58], dependency maps [57], and enrichment maps [49] of previously prioritized genes by the Consensus Strategy [59], the Pan-Cancer Atlas project [6064], the Pharmacogenomics Knowledgebase (PharmGKB) [2], and the Cancer Genome Interpreter [65]. The druggable prediction of BC proteins through ML approaches will provide us relevant information regarding potential biomarkers, therapeutic targets and future clinical trials, avoiding ethnicity bias and improving cancer pharmacogenomics and precision medicine worldwide [6676].…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study [44], we revealed essential proteins associated with BC pathogenesis through deep analyses of genetic alterations, signaling pathways [52], protein-protein interaction networks [55, 56], protein expression [57, 58], dependency maps [57], and enrichment maps [49] of previously prioritized genes by the Consensus Strategy [59], the Pan-Cancer Atlas project [6064], the Pharmacogenomics Knowledgebase (PharmGKB) [2], and the Cancer Genome Interpreter [65]. The druggable prediction of BC proteins through ML approaches will provide us relevant information regarding potential biomarkers, therapeutic targets and future clinical trials, avoiding ethnicity bias and improving cancer pharmacogenomics and precision medicine worldwide [6676].…”
Section: Resultsmentioning
confidence: 99%
“…Canonical pathways of scTPA contain 51,210 human and 1,762 mouse pathways from seven widely used pathway databases including BioCarta, HumanCyc (13), KEGG (14), PANTHER (15), PharmGKB (16), Reactome (17), SMPDB (18), which were retrieved from R package graphite (19). Notably, these literature-curated pathways were grouped into 6 different catalogs including general pathways, metabolic pathways, signaling and regulatory pathways, genome maintenance pathways, drug & small molecules pathways and cancer pathways (20).…”
Section: Biological Pathwaysmentioning
confidence: 99%
“…The CGI flags genomic biomarkers of drug response with different levels of clinical relevance 38 . Lastly, PharmGKB is a comprehensive resource that curates and spreads knowledge of the impact of clinical annotations on BC drug response 37,40 . PharmGKB collects the precise guidelines for the application of pharmacogenomics in clinical practice published by the European Society for Medical Oncology (ESMO), the National Comprehensive Cancer Network (NCCN), the Royal Dutch Association for the Advancement of Pharmacy (DPWG), the Canadian Pharmacogenomics Network for Drug Safety (CPNDS) and the Clinical Pharmacogenetics Implementation Consortium (CPIC) 41–44 .…”
Section: Introductionmentioning
confidence: 99%